Antigen-specific T-cell downregulation by human dendritic cells following blockade of NF-kappaB. - Calder, V; Bondeson, J; Brennan, F; Foxwell, B; Feldmann, M (2003)
Dendritic cells (DCs) are important for presenting antigen to T cells, especially naïve T cells. It has recently been shown that blocking the transcription factor, nuclear factor kappa B (NF-kappaB) in human DCs inhibited the mixed leukocyte reaction. The aim of this study was to investigate the effect of blocking NF-kappaB in DCs during presentation of antigen to memory T cells in vitro. Peripheral blood monocytes were differentiated into immature DCs with interleukin-4 (IL-4) and granulocyte-macrophage colony-stimulating factor, and pulsed with an immunogenic tetanus toxoid peptide. Upon maturation, the antigen-pulsed DCs were highly effective in presenting antigen to autologous T cells. However, stimulation with antigen-pulsed DCs overexpressing IotakappaBetaalpha, the endogenous inhibitor of NF-kappaB, led to a significant reduction in T-cell proliferation, and decreased production of interferon-gamma, IL-4 and IL-10, whereas transforming growth factor-beta production was low throughout. There was a significant increase in apoptosis of antigen-specific T cells, even in the presence of IL-2, which was not found in resting T cells. Similar findings were observed using a proteasome inhibitor to block NF-kappaB. The effective downregulation of antigen-specific T-cell responses following blockade of NF-kappaB in DCs could be a useful approach for immunomodulating inflammatory T-cell responses.